The Age of Aidans: Cognitive Underpinnings of a New Trend in English Boys' Names. (3rd July 2019) - MacAulay, Lauren; Siddiqi, Daniel; Toivonen, Ida
Abstract : Several sources have recently reported a trend in North American English boys' names. According to this trend, a disproportionate number of boys' names contain a final syllabic nasal. This paper presents two studies that investigate this observation systematically. A corpus linguistic study of the most popular names in Ontario and the USA revealed that around 40% of English boys' names fit this pattern, which has been called "the Age of Aidans". The second study was a lexical decision task. It was modeled after previous research on sound symbolism (phonosemantics). This experiment demonstrated that speakers preferred pseudo-names for boys that fit the "Age of Aidans"pattern. Taken together, the two studies suggest that final syllabic nasals can be compared to phonesthemes. Current North American speakers of English may perceive disyllabic names ending in syllabic nasals as "good" boys' names.